Molecular systematics of the tribe Prismatomerideae (Rubiaceae) and its taxonomic consequences, with notes on the importance of the inflorescence morphology for species‐group recognition in Rennellia. Issue 2 (28th December 2020) - Razafimandimbison, Sylvain G.; Wong, Khoon‐Meng; Rydin, Catarina
Abstract: Tropical Asia is one of the centers of species diversity of flowering plants, in particular the coffee family (Rubiaceae). Prismatomerideae (the Psychotrieae alliance, subfamily Rubioideae) are a mostly Southeast Asian tribe encompassing four genera of shrubs and small trees (monospecific Gentingia and Motleyia, Prismatomeris with 16 spp., Rennellia with 4–5 spp.). We conducted molecular phylogenetic analyses of this group based on the nuclear and plastid sequence data from six markers and using Bayesian inference. The main goal was to produce a robust phylogeny of the tribe, which was subsequently used to (1) reassess its monophyly and phylogenetic position within the Psychotrieae alliance; (2) rigorously test the monophyly of Prismatomeris and Rennellia ; (3) assess the phylogenetic relationships between the genera; and (4) evaluate the phylogenetic value of the inflorescence type currently used for species recognition in Rennellia . Motleyia was not sequenced due to the lack of material, and therefore its affinity with the other genera was assessed based on morphology. The tribe was supported as monophyletic and resolved as sister to the (Gaertnereae (Mitchelleae‐Morindeae)) clade. The monophyly of Prismatomeris sensu Johansson was strongly supported, but we argue for the merging of the monospecific genus Motleyia into Prismatomeris based on their strong morphological similarities coupled with the paraphyly of Prismatomeris with respect to Motleyia . Rennellia was strongly supported as paraphyletic with respect to Gentingia . We propose the transfer of the monospecific genus Gentingia to Rennellia, also consistent with their strong morphological resemblance. Prismatomerideae were resolved in two major sister lineages, the Prismatomeris and Rennellia clades, corresponding to our broadly delimited Prismatomeris and Rennellia . Three well‐supported and morphologically distinct subclades were identified within Rennellia s.l., of which one was represented by Rennellia subsessilis, with sessile and reduced umbel‐like inflorescences bearing two to four flowers. The other two subclades have compound spike‐like (or sub‐raceme‐like) and raceme‐like inflorescences, an important distinction in species‐group recognition. We conclude that inflorescence type shows a strong phylogenetic signal and is, therefore, a reliable feature for recognizing groups of species in Rennellia . Additional taxonomic characters are, however, needed for teasing apart closely related species with the same inflorescence types. Subsequent to our taxonomic revision, the tribe Prismatomerideae comprises two genera: Prismatomeris and Rennellia . One and two new combinations, respectively, are presented, bringing the total number of species in the tribe to 25, of which 17 are in Prismatomeris and 8 in Rennellia . A new species key to Rennellia s.l. is presented.